(untitled) (Anwer Khan Modern Medical College Journal, 2013)
Perthes’ disease is a disorder of the hip joint in children. Femoral head became softens, flattened or deformed because of the lack of blood supply of unknown cause. It is a very rare cause of bilateral avascular necrosis of the head of the femur, which can easily diagnosed by clinical correlation with the X-ray pelvis findings. Here we present a typical case of Perthes disease, who was finally diagnosed after a long periods of time. In Perthes disease early detection is very important to preserve, restore the femoral head, relieve pain and prevent long term osteoarthritis. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13684 AKMMC J 2013: 4(1): 40-41